Boosting sluggish climate policy: Endogenous substitution, learning, and energy efficiency improvements - Lucas Bretschger; Matthias Leuthard; Alena Miftakhova (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
There is widespread concern that climate policy is moving too slowly and that decarbonization of economic development is coming too late for effective climate protection. We analyze three different effects that emerge endogenously during decarbonization and amplify current policies: growing substitutability of dirty inputs with clean inputs, learning and scale effects in new renewables, and efficiency improvements in the application of energy. We employ the CITE simulation model, a computable general equilibrium (CGE) model with endogenous growth dynamics, to represent the macroeconomic framework of climate policy, calibrate the impacts, and obtain quantitative results. We use data for the Swiss economy and find that all three effects significantly accelerate decarbonization and markedly reduce the costs of climate policy, with increasing substitutability having the strongest impact. Targeted policies such as subsidies to clean energy and R&D may amplify these effects and thereby speed up the transition towards a carbon-free economy.
Keywords: O31; O32; Q43; Q54; Q55; Q58; 330; CGE modelling; endogenous growth; energy efficiency; learning; elasticity of substitution; innovation; climate policy